Single-Cell RNA Sequencing Analysis Reveals Sequential Cell Fate Transition during Human Spermatogenesis - Wang, Mei; Liu, Xixi; Chang, Gang; Chen, Yidong; An, Geng; Yan, Liying; Gao, Shuai; Xu, Yanwen; Cui, Yueli; Dong, Ji; Chen, Yuhan; Fan, Xiaoying; et al. (Cell stem cell, 2018)
Spermatogenesis generates mature male gametes and is critical for the proper transmission of genetic information between generations. However, the developmental landscapes of human spermatogenesis remain unknown. Here, we performed single-cell RNA sequencing (scRNA-seq) analysis for 2,854 testicular cells from donors with normal spermatogenesis and 174 testicular cells from one nonobstructive azoospermia (NOA) donor. A hierarchical model was established, which was characterized by the sequential and stepwise development of three spermatogonia subtypes, seven spermatocyte subtypes, and four spermatid subtypes. Further analysis identified several stage-specific marker genes of human germ cells, such as HMGA1, PIWIL4, TEX29, SCML1, and CCDC112. Moreover, we identified altered gene expression patterns in the testicular somatic cells of one NOA patient via scRNA-seq analysis, paving the way for further diagnosis of male infertility. Our work allows for the reconstruction of transcriptional programs inherent to sequential cell fate transition during human spermatogenesis and has implications for deciphering male-related reproductive disorders. [Display omitted] •High-quality single-cell RNA-seq of human testicular cells reveals 17 cell clusters•Key signature genes and developmental trajectory of male germ cells were revealed•FGF and BMP pathways may play important roles for human spermatogonial stem cells•Single-cell RNA-seq analysis revealed molecular basis of the defects of a NOA patient Single-cell RNA sequencing of 2,854 testicular cells reveals critical biological features of the sequential and stepwise development of spermatogonia, spermatocytes, and spermatids during human spermatogenesis. Moreover, altered transcriptional patterns were identified in a NOA patient, supporting the value of scRNA-seq for diagnosis and dissecting the underlying mechanisms of male infertility.